País de São Saruê: o paraíso terrestre na literatura de folhetos - Maia, Caroline Sandrise dos Santos (2019)
The creation of imaginary societies to supply the real needs is a characteristic of human beings. Therefore, it is common to f ind literary works that present us true earthly paradises in their plots, places that are full of everything that is scarce for the majority of the population in the real world, such as Cocanha and São Saruê. Stories about Cocanha, a country designed by th e medieval imagination, where who sleeps the most earns the most, circulated orally around Europe in the mid 12th century and were set in the Fabliau da Cocanha in the 13th century. Similarly, in northeastern of Brazil, the country of São Saruê, the best p lace in the world, appears in the cordel leaflets. Thus, this dissertation, with a qualitative approach, aims to analyze the Fabliau da Cocanha comparatively, the leaflets Viagem a São Saruê (1956), by Manoel Camilo dos Santos, O pé de macaxeira rosa do pa ís São Saruê (s/d), Um passeio a São Saruê (1974) and O sonho de um poeta no país São Saruê (s/d), by José Costa Leite, As terra de São Saruê (1976), by Minelvino Francisco Silva, Passeio em São Merdoê (s/d), by Manoel Messias Belizario Neto, Viagem ao paí s de São Cornélio (2001), by Klévisson Viana, and Viagem à Santa Vontade (2008), by Maria Godelivie, using the theoretical precepts of Discursive Tradition (DT) to investigate how the narrative about Cocanha resignifies itself according to the cultural con text in which it operates, as well as the structural recurrences presented in the cordel leaflets that have as their theme the country of São Saruê. To support our discussion, we use the following bibliography: Abreu (1993, 2006), Ayala (1997, 2010, 2016), Franco Junior (1998a, 1998b), Kabatek (2006), Le Goff (2009), Longhin (2014) and Terra (1983).